The Role of Psychological and Physiological Factors in Decision Making under Risk and in a Dilemma - Fooken, Jonas; Schaffner, Markus (Frontiers in Behavioral Neuroscience, 2016)
Different methods to elicit risk attitudes of individuals often provide differing results despite a common theory. Reasons for such inconsistencies may be the different influence of underlying factors in risk-taking decisions. In order to evaluate this conjecture, a better understanding of underlying factors across methods and decision contexts is desirable. In this paper we study the difference in result of two different risk elicitation methods by linking estimates of risk attitudes to gender, age and personality traits, which have been shown to be related. We also investigate the role of these factors during decision-making in a dilemma situation. For these two decision contexts we also investigate the decision-maker's physiological state during the decision, measured by heart rate variability (HRV), which we use as an indicator of emotional involvement. We found that the two elicitation methods provide different individual risk attitude measures which is partly reflected in a different gender effect between the methods. Personality traits explain only relatively little in terms of driving risk attitudes and the difference between methods. We also found that risk taking and the physiological state are related for one of the methods, suggesting that more emotionally involved individuals are more risk averse in the experiment. Finally, we found evidence that personality traits are connected to whether individuals made a decision in the dilemma situation, but risk attitudes and the physiological state were not indicative for the ability to decide in this decision context.